Aggression and Harm-Avoidant Trait Impede Recovery From Internet Gaming Disorder - Lee, Seung-Yup; Lee, Hae Kook; Bang, Soo-young; Jeong, Hyunsuk; Yim, Hyeon Woo; Kweon, Yong-Sil (Frontiers in Psychiatry, 2018)
Background Relatively little is known about which neuropsychological factors promote recovery from Internet gaming disorder (IGD). Methods With informed consents, a cohort study was conducted in Seoul metropolitan area, South Korea, to investigate the course of IGD in youths. At baseline, we assessed psychosocial measures and gaming related measures such as Young’s Internet Addiction Test (IAT) and the Aggression Questionnaire. The Balloon Analogue Risk Task was also performed to study risk-taking behavior. A total of 60 subjects demonstrating three or greater criteria in the diagnostic interviews on IGD and the IAT score of 50 or above were included. After brief parental coaching at baseline, the participants were followed up at three and six months (n=31). The baseline characteristics were compared between the non-improved group (<10% improvement in IAT score) and the improved group (≥30% improvement in IAT score) using Mann-Whitney U test or chi-squared tests with a two-tailed statistical significance of 0.05. Results The non-improved group and the improved group did not demonstrate significant differences regarding demographics or the IAT scores at baseline. However, the IAT scores were significantly higher in the non-improved group at both three months and six months. The non-improved group was also more likely to display higher aggression and harm avoidance than the improved group at baseline. Discussion Youths with excessive gaming problems should be evaluated for aggression and harm avoidance since they contributed to a worse prognosis. For those with high aggression or harm avoidance, more active therapeutic interventions should be considered.